BODY CHECKING PRACTICES AS A MECHANISM OF BODY DISCIPLINE IN THE SOUTH JAKARTA BLINK COMMUNITY A MICHEL FOUCAULT PERSPECTIVE - Adna Fika Ardelia; Andhika Ramadhan Kusuma; Rifma Ghulam Dzaljad (Media Inovasi Pendidikan dan Publikasi, 2026)
The digital era and the globalization of popular culture through the Korean Wave (Hallyu) phenomenon have not only altered entertainment consumption patterns but have also constructed how individuals perceive identity and body image through the aesthetic standardization of the K-Pop industry. This study aims to analyze body checking practices as a body discipline mechanism within the South Jakarta BLINK community from the perspective of Michel Foucault's power theory. Utilizing a qualitative approach with a descriptive case study method, this research involved six informants aged 20–24 years selected through purposive sampling based on their active involvement in the BLACKPINK fandom and high intensity of K-Pop content consumption. Data were gathered through in-depth interviews and documentation, and subsequently analyzed using the Miles and Huberman interactive model, which comprises data reduction, data display, and conclusion drawing. The findings demonstrate that the representation of the ideal body exhibited by BLACKPINK members has undergone a process of naturalization and has been internalized by fans as a taken-for-granted social norm. Furthermore, body checking practices, manifested in repetitive actions such as constant mirror-gazing, weighing body mass, and comparing physical attributes with the idols, do not stem from direct coercion but rather manifest as a form of voluntary self-regulation. Within a Foucauldian perspective, this phenomenon illustrates the operation of disciplinary power and self-surveillance, wherein social media functions as a digital panoptic space. The novelty of this research lies in its deconstruction of body checking behavior, shifting it from a mere individual psychological symptom to a product of power relations and body discipline working subtly within an urban fan community ecosystem.